Strategies for improved endothelial cell adhesion in microphysiological vascular model systems - Jingyi Zhu; Halie L. Hotchkiss; Kevin L. Shores; George A. Truskey; Stacey A. Maskarinec (PLoS ONE, 2025)
Human tissue-engineered blood vessels (TEBVs) have been applied as model systems to study a wide range of vascular diseases including Hutchinson-Gilford Progeria Syndrome and early atherosclerosis. Central to the utility of TEBVs as an in vitro blood vessel model is the maintenance of a functional endothelium under physiologically relevant shear stresses. Establishing and maintaining a confluent endothelial monolayer is challenging. In this protocol, we outline an optimized procedure for the endothelialization of TEBVs. We optimized the following key conditions affecting endothelial cell (EC) adherence in the vessel: EC seeding density, rotation time, and the application of perfusion. This protocol results in TEBVs with sustained EC luminal coverage that demonstrate alignment in the direction of applied flow and responsiveness to inflammatory stimuli. To facilitate rapid screening of EC coverage during the fabrication and perfusion steps, we re-designed TEBV chambers to include a viewing window that allows for efficient monitoring and assessment of the endothelialization process using fluorescence microscopy. By identifying key factors that affect EC attachment in TEBVs, this protocol may serve as a valuable resource for researchers seeking to achieve successful endothelialization of engineered blood vessel constructs.